Effect of Cruciferous Vegetable Intake on Oxidative Stress Biomarkers: Differences by Breast Cancer Status. (21st April 2017) - Wirth, Michael D.; Murphy, E. Angela; Hurley, Thomas G.; Hébert, James R.
ABSTRACT: This post hoc analysis examined cruciferous vegetable intake on urinary oxidative metabolites in postmenopausal women. Intervention participants ( n = 69) received cruciferous vegetables (≥14 cups/week) during a 3-week period. First morning urine measured 8-isoprostane and 8-hydroxy-2′-deoxyguanosine. Dietary intake was estimated using 24-h recalls. When stratified by history of breast cancer, those with breast cancer had significantly lower post-intervention urinary 8-hydroxy-2′-deoxyguanosine values in the intervention arm versus. the control arm (1.1 ng/mL vs. 3.2 ng/mL, p = .01) after adjustment for baseline 8-hydroxy-2′-deoxyguanosine. This was not observed in those without breast cancer. Further work is needed to understand the role of breast cancer in these relationships.